Cardiovascular risk factors in adults 80 years of age or older - Ruiz Mori, Enrique (2015)
Objective: In Peru, the 80 year old and older population is increasing and cardiovascular diseases are the leading cause of death. The aim of the study was to analyze the cardiovascular risk factors in octogenarians. Material and Methods: This is a descriptive, observational, cross prevalence research, conducted in March 2015 in Lima. Aquestionnaire on cardiovascular risk factors was used; blood pressure, weight, height and body mass index, in people 80 years of age or older. Results: 969 subjects were evaluated, of whom 562 (58%) were women and 407 (42%) were male; with an average age of84.2 years; predominant age group of 80-84years 60.5%. 427 cases were hypertensive (44.1%), this was more common in women (62.2%).9% of the study population (87 cases) were smokers; being more common in men (64%) (p = 0.000009). 220 subjects (22.7%) with hypercholesterolemia were registered, this being more common in women; 139patients (63.2%), without statistical significance. Diabetes was reported in 11.5% of the studied sample (111 patients) and it was more frequent in women (68.5%)(p = 0.018).According to BMI values, 537 subjects (55.4%) had a BMI <25,while 33.8% of the population (328) were overweight and 10.7% were obese, which was more prevalent in women (70, 2%) (p = 0.028).In the hypertensive population, 87% had drug treatment, of which 65% were controlled. 26.5% (257cases) had two risk factors and 13.1% (127) had three or more risk factors. Conclusion: The most frequent factor of cardiovascular risk has been hypertension, predominantly in women. 40% of the evaluated subjects had two or more risk factors. 87% of hypertensive patients received drug treatment and65% of them were controlled.